The Role Of Job Satisfaction In Mediation The Influence Of Training And Competencies On Performance Moderate By Work Commitment (Study of Kolaka Regency Regional Secretariat Employees) - Kasmawati, Kasmawati; Samdin, Samdin; Nurwati, Nurwati; Nasrul, Nasrul (Journal of Neonatal Surgery, 2025)
This research aims to analyze: the influence of training on job satisfaction and employee performance , the influence of competency on job satisfaction and employee performance , the influence of job satisfaction on employee performance , the role of Job Satisfaction in mediating the influence of Training and competency on Employee Performance , the role of Work Commitment in moderating the influence of Training on Employee Performance , the role of Work Commitment in moderating the influence of Competency on Employee Performance , The role of Work Commitment in moderating the influence of Satisfaction on the Performance of Kolaka Regency Regional Secretariat Employees.The design of this research is explanatory research with a survey approach. The sampling technique used purposive sampling, with a total sample of 114 employees . This research uses descriptive and inferential analysis with the analysis used, namely Structural Equation Modeling (SEM) with the SmartPLS ( Partial Least Square ) program Version 4 .The research results show that Training has a positive and significant effect on job satisfaction , Competence has a positive and significant effect on job satisfaction , Training has a positive and significant effect on performance , Competence has a positive and significant effect on performance , Job satisfaction has a positive and significant effect on performance , Employee job satisfaction is not yet a mediation that has a significant impact (pseudo-mediation) on improving performance , Employee job satisfaction is not yet a mediation that has a significant impact (pseudo-mediation) on improving performance , Work commitment is not significant in moderating the effect of training on performance , Work commitment positively and significantly moderates the influence of competence on performance . Work commitment positively and significantly moderates the influence of job satisfaction on performance .